The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1063/1.342120
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear properties of Rayleigh and Stoneley waves in solids

Abstract: Bulk wave reflection formulas are extended to the surface-wave case, considering Rayleigh and Stoneley waves in terms of refracted inhomogeneous longitudinal and transversal waves, linked by the surface coupling. In this manner, a physical mechanism of second-harmonic generation process is clearly shown. The analytical expressions and physical pictures of Rayleigh- and Stoneley-wave harmonic generation have been derived in a second-order approximation. The solution shows that the second-harmonic surface waves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 8 publications
0
19
0
1
Order By: Relevance
“…For the ideally bonded interface, a general approach to the boundary acoustic nonlinearity (nonlinear reflection technique) was first developed by Shui and Solodov [116]. It was shown that generally all the waves existing at the interface contributed into the interface acoustic nonlinearity.…”
Section: Nonlinear Nde Using Contact Acoustic Nonlinearitymentioning
confidence: 99%
See 1 more Smart Citation
“…For the ideally bonded interface, a general approach to the boundary acoustic nonlinearity (nonlinear reflection technique) was first developed by Shui and Solodov [116]. It was shown that generally all the waves existing at the interface contributed into the interface acoustic nonlinearity.…”
Section: Nonlinear Nde Using Contact Acoustic Nonlinearitymentioning
confidence: 99%
“…Because of the lack of dispersion, the finite-amplitude method, which uses SAWs, can be applied for a quantitative determination of β 2 , or the third-order constants, using the analytical expressions for the SAW second-harmonic amplitude obtained in ref. 116 and modified (if needed) to account for the attenuation from (30).…”
Section: Experimental Arrangementsmentioning
confidence: 99%
“…The relation has been derived in our previous work [2] as where Uz((i)) and Uz(2(i)) are the fundamental and second order harmonic amphtudes of a Rayleigh wave displacement; kj^, k, and k^ are the Rayleigh, longitudinal and shear wave numbers. This equation can be derived from the full perturbation analysis of Shui and Solodov [7]. It is noted that Eq.…”
Section: Acoustic Nonlinearity Parameter In Terms Of Surface Normal Dmentioning
confidence: 98%
“…이들 중, 마스크 슬릿을 이용한 기법은 매우 간편하면서도 효과적인 방법이며, Jhang은 이 기법을 통하여 발생된 협대역의 레이저 여기 표면파의 음향 비선형 특성을 계측하였다 [12]. 특 히, Shui와 Solodov는 종파보다도 표면파에 의한 고조파발생이 약 10 3 배나 크다는 것을 물리적이 고 분석적으로 보고하였다 [13].…”
Section: 서 론unclassified